Іншомовна освіта в Україні: основні тенденції модернізаційних процесів - Мельник, Р. (Філологічний дискурс, 2018)
У статті аналізуються процеси модернізації сучасної іншомовної освіті в Україні, дається стисла характеристика основних принципів оволодіння іноземною мовою та інноваційних методів навчання іноземних мов, зазначаються певні проблеми у системі вітчизняної іншомовної парадигми. The article describes the main goal of foreign language education, which implies not only mastering situational, thematic and partner-oriented communicative competences, but also the ability of intercultural communication. The processes of modernization of contemporary foreign education in Ukraine that involves the use of personality-oriented, activity, interdisciplinary and intercultural approaches being successfully used in the system of foreign language education in Central European countries are analyzed. The main principles of the joint innovative project of the Ministry of Education and Science of Ukraine and the British Council, «A New Generation School Teacher», piloted on the basis of more than 10 Ukrainian institutions of higher education, are characterized. The purpose of the project is to test a new model of «cross-cutting» methodological training of future teachers of English. The brief description of innovative methods of teaching foreign languages such as discussion, brainstorming, dramatization, language portfolios, mixed learning, case method, interactive method, etc. is given, and the basic principles of mastering a foreign language like sequence, consistency, reflection, variability, activity and autonomy are considered. It is noted that despite the significant achievements, the condition of domestic foreign intercultural education needs further transformations considering pan- European experience in the field of foreign language education, with the aim of forming and developing communicative skills of the individual, developing integrated curricula and textbooks in a foreign language, intensive development of intercultural communication in educational space.